Effects of Leadership Development Program on Self-Efficacy in School Health Promotion, Thailand (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
Objective: To examine the effects of a health leadership development program on self-efficacy in health screening and life safety in school, among health education major college students. Methods: In this research, 22 health education major college students from the 2nd year of Srinakharinwirot university, Thailand volunteered to join the program. Students worked as a team to create a health promotion program (1 program per team) for the nearby community. Self-efficacy in health screening and life safety was measured using a self-administered questionnaire before and after the program. Data were analyzed using descriptive statistics such as mean and standard deviation, as well as Wilcoxon matched-pairs signed-rank test . Results: After program participation, self-efficacy in health screening and life safety increased significantly from baseline (P < 0.05). Conclusion: Health promotion leadership program helps improves knowledge and self-efficacy. The Health Education department should encourage the students to learn and practice from direct experience to become quality health promotion leaders.